Chemical mechanism for the decomposition of CH3NH2 and implications to interstellar glycine. Issue 1 (24th November 2020) - de Jesus, Diego N; da Silva, Jean M B A; Tejero, Tatiane N; de Souza Machado, Gladson; Xavier, Neubi F; Bauerfeldt, Glauco F
ABSTRACT: Complex organic molecules from extraterrestrial source are expected to have contributed to the Early Earth chemistry. Methylamine (CH3 NH2 )has already been observed in the interstellar medium (ISM) and is generally related to the formation of glycine, although the latter has not been identified in the ISM yet. In this work, a chemical model for CH3 NH2 was investigated, comprising twenty-eight reactions and including reactions involving NH3 and HOOC, aiming to understand the main routes for formation and decomposition of methylamine and also to infer about the chemical behaviour of glycine in the ISM. Calculations were performed at the CCSD(T)/aug-cc-pVTZ//M06-2X/aug-cc-pVTZ level and rate coefficients were calculated adopting the canonical variational transition state theory (CVTST), in the temperature range 100 to 4000 K, including tunnelling effects. Starting from HCN, the preferred pathway for methylamine formation is through consecutive hydrogenation steps, forming CH2 N, CH2 NH, and CH2 NH2 intermediates. Considering the decomposition, dissociation into CH3 and NH2 is the most favourable step. NH3 and HCN are common compounds in interstellar ice analogues and react producing NH2 and CH2 N through NH2 NCH2 and H2 NCH2 N intermediates. The latter is proposed here and spectroscopic data for any future experimental investigation are given. Finally, an extension to the ISM glycine chemistry is explored and routes to its formation, from the simplest compounds found in interstellar ices, are proposed.